Technical development of countercyclical capital buffer implementation in Mongolia's banking sector - Enkhbaatar Oyungerel; Urangoo Erdenebileg (Graduate Institute of International and Development Studies, 2025)
This paper attempts to develop a framework for implementing the Countercyclical Capital Buffer (CCyB) in Mongolia's banking sector by identifying early warning indicators of systemic risk and examining the impact of capital adequacy on bank lending. Using quarterly data from 2000 to 2024, the study employs signaling (area under the receiver operating characteristic curve), logit regression, decision tree analysis, and panel regression techniques. Results show that credit-to-GDP gaps, external and fiscal imbalances are strong predictors of banking crises. Additionally, a one-percentagepoint increase in the capital adequacy ratio reduces loan-to-asset ratio by 0.74 percentage points, with the effect more pronounced among larger banks. These findings support the case for a tailored, data-driven CCyB framework in Mongolia and offer broader implications for countercyclical policy design in small, open and commoditydependent economies.
Keywords: E58; G28; G32; C23; 330; countercyclical capital buffer (CCyB); capital adequacy ratio; bank lending; early warning indicators; financial stability